2012
DOI: 10.1021/ac302409a
|View full text |Cite
|
Sign up to set email alerts
|

Selected Ion Flow Tube-MS Analysis of Headspace Vapor from Gastric Content for the Diagnosis of Gastro-Esophageal Cancer

Abstract: Gastric content is a complex biofluid within the human stomach which has an important role in digestive processes. It is believed that gastric content may be a contributory factor in the development of upper gastro-intestinal diseases. In this work, selected ion flow tube mass spectrometry (SIFT-MS) has been applied to the quantification of volatile organic compounds (VOCs) in the headspace vapor of gastric content samples, which were retrieved from three groups of patients, including those with gastro-esophag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
64
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(75 citation statements)
references
References 39 publications
8
64
3
Order By: Relevance
“…Once tyrosine has been released into the gastric content, the action of tyrosine phenol-lyase from the microbiome could convert tyrosine to phenol causing increased concentrations within gastric content. This is in keeping with the findings of previous studies showing increased phenolic compound concentrations within gastric content of patients with gastroesophageal cancer (17). Increased phenol concentrations have also been observed in the exhaled breath of patients with gastroesophageal cancer (15).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Once tyrosine has been released into the gastric content, the action of tyrosine phenol-lyase from the microbiome could convert tyrosine to phenol causing increased concentrations within gastric content. This is in keeping with the findings of previous studies showing increased phenolic compound concentrations within gastric content of patients with gastroesophageal cancer (17). Increased phenol concentrations have also been observed in the exhaled breath of patients with gastroesophageal cancer (15).…”
Section: Discussionsupporting
confidence: 92%
“…This reaction was first discovered in bacterial cultures by Kakihara and Ichihara (14). Phenolic compounds are potential biomarkers of gastroesophageal cancer with altered concentrations observed within exhaled breath (15), urine (16) and gastric content (17).…”
Section: Introductionmentioning
confidence: 99%
“…There are several lines of prior studies demonstrating that volatile sulfur compounds, including H 2 S, are increased in patients with certain forms of cancer (31,32), although its sources or biological functions remained unexplored. In addition, several prior studies demonstrated an increase in CBS expression in various forms of human cancer (33)(34)(35), although the functional consequence of these observations remained unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence from recent studies demonstrate significant increases in exhaled H 2 S levels in cancer patients (4,48,66,140); however, the identification of its biological source was not investigated. In addition, elevated urinary thiosulfate (the stable breakdown product of H 2 S) levels were found in prostate cancer patients; the mean thiosulfate levels in prostate cancer patients were almost 50 times higher than in the control groups and 5 times higher than in patients with benign prostatic hyperplasia (19).…”
Section: Increased Expression Of Cbs And/or Increased Production Of Hmentioning
confidence: 99%